PERANAN PKK DALAM MEMANFAATKAN POTENSI KEBUDAYAAN DAERAH DI DESA WIRATA AGUNG LAMPUNG TENGAH - Iketut Susana; Holilulloh Holilullah; Yunisca Nurmalisa (FKIP Unila, 2012)
The purpose of this study is to explain the role of mother group PKK in the Field of Culture in Connection with Potential Utilize Regional Cultural at Wirata Agung Village Kecamatan Seputih Mataram Central Lampung in 2013. The method used is descriptive method, the respondents in this study is the Great Mother PKK in Wirata Agung village with samples from 36 people. Basic techniques used in data collection is using questionnaires. Based on the analysis of data it can be seen that the Development Capital Group Family Welfare (PKK) in Wirata Agung Village is quite instrumental in harnessing the potential of the regional culture. For indicators motivate parents to care about the local culture, mobilize communities in an effort to preserve local culture, people knowledgeable about the potential of the regional culture and society have the skills to preserve local culture, the role of PKK groups in the category of quite a role.Keywords: group PKK and Potential Cultural Capital Region.